PENGUATAN IMPLEMENTASI EVALUASI KURIKULUM PENDIDIKAN AGAMA ISLAM DALAM KONTEKS KURIKULUM MERDEKA: KAJIAN LITERATUR - Syarifah Sriwahyuni; Julhadi Julhadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Curriculum evaluation is a crucial component in improving the quality of Islamic Religious Education (PAI). It is not only positioned as the final stage of curriculum development but also serves as a basis for continuous improvement in teaching implementation. This study aims to analyze the implementation of an evaluation-based PAI curriculum in the planning, learning process, and student assessment aspects. A literature review method was used focusing on curriculum evaluation theory and its implementation in educational institutions. The results indicate that implementing an evaluation-based curriculum requires PAI teachers to continuously reflect, monitor, and comprehensively assess the learning process to provide constructive feedback. Therefore, evaluation becomes an instrument that supports the realization of a more adaptive and responsive curriculum aligned with students' needs and societal demands.Keywords: curriculum evaluation, Islamic religious education, implementation, assessment